The Relative Age Effect at different age periods in soccer: A meta-analysis - Bozdech, M.; Agricola, A.; Zhanel, J. (Perceptual and Motor Skills, 2023)
In the selection of young athletes, earlier-born adolescents often leverage their temporary biological advantage over their later-born peers from the same cohort, giving rise to the phenomenon known as the Relative Age Effect (RAE). In this study, we delved into the complexities of the RAE in soccer by reviewing 563 independent research samples across 90 articles. Our analysis showed that age period and performance level are pivotal factors influencing the magnitude of the RAE. The adolescent age period emerged as a significant RAE determinant, showcasing the highest effect size magnitudes in our findings. Among athletes of different performance levels, adult European soccer players have been extensively studied, and they have exhibited the most pronounced RAE magnitudes. Intriguingly, our findings reveal another compelling trend: the frequency of players born early versus late in the eligible birth year escalated as player performance levels increased, particularly during adolescence. Coaches and players appear to capitalize unconsciously on this maturational advantage, though this strategy wanes post-adolescence. While there are currently no penalties for this team selection practice, our findings stress the need for coaches to comprehend the ramifications of selecting athletes with an age bias. We offer insights into RAE complexities, highlight the synergy of age and performance in these transitory advantages, and advance arguments for more fairly selecting and developing youth athletes.